The chemical composition of the aerial parts of Stachys spreitzenhoferi (Lamiaceae) growing in Kythira Island (Greece), and their antioxidant, antimicrobial, and antiproliferative properties. (November 2022) - Napolitano, Assunta; Di Napoli, Michela; Castagliuolo, Giusy; Badalamenti, Natale; Cicio, Adele; Bruno, Maurizio; Piacente, Sonia; Maresca, Viviana; Cianciullo, Piergiorgio; Capasso, Lucia; Bontempo, Paola; Varcamonti, Mario; et al.
Abstract: The Stachys L. genus has been used in traditional medicine to treat skin inflammations, stomach disorders, and stress. The aim of this study was to investigate the chemical profile and biological activity of the methanolic extract of Stachys spreitzenhoferi Heldr. (Lamiaceae) aerial parts, collected on the island of Kythira, South Greece. The analysis by liquid chromatography coupled with electrospray ionization and high-resolution mass spectrometry [LC-(−)ESI/HRMS n ] of the methanol extract revealed the occurrence of thirty-six compounds - flavonoids, phenylethanoid glycosides, iridoids, quinic acid derivatives, aliphatic alcohol glycosides, and oligosaccharides – highlighting the substantial presence, as main peaks, of the iridoid melittoside (2 ) along with flavonoid compounds such as 4′- O -methylisoscutellarein mono-acetyl-diglycoside/chrysoeriol mono-acetyl-diglycoside (24 ), trimethoxy- (35 ) and tetramethoxyflavones (36 ). This extract was tested for its antimicrobial properties against Gram-positive and negative pathogenic strains. The extract was not active against Gram-negative bacteria tested, but it possessed a good dose-dependent antimicrobial activity towards S. aureus (MIC: 1.0 mg/mL) and L. monocytogenes (MIC: 1.0 mg/mL) Gram-(+) strains. Furthermore, this extract has been tested for its possible antioxidant activity in vitro . In particular, it has been shown that these molecules cause a decrease in DPPH, ABTS, and H2 O2 radicals. The extract of S. spreitzenhoferi exhibited anti-DPPH activity (IC50 : 0.17 mg/mL), anti-H2 O2 activity (IC50 : 0.125 mg/mL), and promising antiradical effect with an IC50 value of 0.18 mg/mL for anti-ABTS activity. S. spreitzenhoferi extract caused a decrease in ROS (at the concentration of 200 μg/mL) and an increase in the activity of the antioxidant enzymes SOD, CAT, and GPX in OZ-stimulated PMNs. Furthermore, it exhibited antiproliferative activity against acute myeloid leukemia (U937 cell), causing 50% of cell death at the 0.75 mg/mL. Graphical abstract: Image 1 Highlights: Chemical profile and biological activity of the aerial parts of Stachys spreitzenhoferi Heldr. (Lamiaceae). S. spreitzenhoferi extract exhibits different biological activities. It showed a selective antibacterial action against Gram-positive strains. It caused a decrease in DPPH, ABTS, and H2 O2 radicals. It exhibited antiproliferative activity against cancer cells.